2020
DOI: 10.3390/jcm9124001
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity Patterns and Unplanned Hospitalisation in a Cohort of Older Adults

Abstract: The presence of multiple chronic conditions (i.e., multimorbidity) increases the risk of hospitalisation in older adults. We aimed to examine the association between different multimorbidity patterns and unplanned hospitalisations over 5 years. To that end, 2,250 community-dwelling individuals aged 60 years and older from the Swedish National Study on Aging and Care in Kungsholmen (SNAC-K) were studied. Participants were grouped into six multimorbidity patterns using a fuzzy c-means cluster analysis. The assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 44 publications
(35 reference statements)
1
55
3
1
Order By: Relevance
“…In the current study, we identified five patterns of physical multimorbidity which are generally similar to those reported in previous studies. The most commonly identified disease pattern in previous studies has comprised cardiovascular and metabolic disorders [ 19 , [45] , [46] , [47] , [48] , [49] , [50] ], which is unsurprising considering the shared aetiology of these conditions. In the current study, we identified two cardiovascular patterns which might imply that there are different types of cardiovascular multimorbidity that are influenced by different factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we identified five patterns of physical multimorbidity which are generally similar to those reported in previous studies. The most commonly identified disease pattern in previous studies has comprised cardiovascular and metabolic disorders [ 19 , [45] , [46] , [47] , [48] , [49] , [50] ], which is unsurprising considering the shared aetiology of these conditions. In the current study, we identified two cardiovascular patterns which might imply that there are different types of cardiovascular multimorbidity that are influenced by different factors.…”
Section: Discussionmentioning
confidence: 99%
“…The pain/gastrointestinal cluster we observed included conditions such as back pain, arthritis, and IBS. Several earlier studies also identified disease clusters which comprised musculoskeletal pain, arthritis, and gastrointestinal conditions [ 19 , 45 , 50 ]. Potential common mechanisms underlying this group of conditions includes the use of pain medications [54] , difficulty engaging in physical activity [55] , and potential changes in gut bacteria [56] .…”
Section: Discussionmentioning
confidence: 99%
“…Distinct patterns of multimorbidity have repeatedly been found to be differentially associated with negative health outcomes in the older population [14,15]. For example, when compared with other disease combinations, multimorbidity clusters including cardiovascular and neuropsychiatric diseases have displayed strong associations with functional impairment, hospitalization, and death [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that family medicine could be a solution to the lack of specialists in rural areas, especially in aged societies. Among older patients, the problems of multimorbidity with polypharmacy are prevalent, and comprehensive care is critical for their safety, QOL, and end of life care [ 32 , 33 , 34 ]. Future studies can investigate the effectiveness of family medicine regarding patient’s QOL in multiple settings by adding ICD-11 categories which is revised one of ICD-10.…”
Section: Discussionmentioning
confidence: 99%